Do gender dynamics in intra-household decision making shift with male migration? Evidence from rice-farming households in Eastern India - Ram Mohan, Rohini; Puskur, Ranjitha; Chandrasekar, D.; Valera, Harold Glenn A. (Informa UK Limited, 2023)
This paper unpacks the complex relationship between migration of men and the decision making power of the women who “stay behind” in Bihar, Eastern India. We use mixed methods research design to assess whether women perceive a shift in decision making “authority” between different members in households where men migrate and examine the subjective meanings of these shifts. Using a retrospective survey, we map the extent to which women report shifts in decision making “authority” after the migration of male members. Decision making is examined for various activities classified into four domains: agricultural practices, labor allocation, machinery and purchase of productive assets, and household expenditure and activities. Overall, patterns indicate a nominal change in the proportional distribution of perceived household decision authority for all categories and shift toward joint decision making (by wife and husband) emerging as an important trajectory. Using multinomial regression and interpretative analysis of qualitative findings, the paper sheds light on the role of age, family type, household and migrant characteristics in shaping the direction of shifts, and limiting the transfer of meaningful bargaining power to women. The paper makes a case that the transformation of the patriarchal habitus requires a more substantial transformation of livelihood capitals.